Character’s Analysis in Ego Defense Mechanism due to Trauma and Revenge on Hannibal Rising - Anggraeni, Demarmega Galuh; Widyaningrum, Agnes (Scripta : English Department Journal, 2024)
This study explores the ego defense mechanisms exhibited by the main character in Peter Webber’s film Hannibal Rising, particularly in response to trauma and revenge. Rooted in psychoanalytic theory, the analysis focuses on how the protagonist, Hannibal Lecter, employs various defense mechanisms such as repression, denial, and sublimation to cope with the traumatic events of his past. These mechanisms help him channel his psychological distress into acts of revenge. The study delves deeper into the implications of these defense mechanisms on Hannibal's personality development, examining how trauma shapes his moral descent and fuels his violent tendencies. Additionally, the complex interplay between trauma, psychological defenses, and the protagonist’s relentless drive for retribution is explored, offering a nuanced understanding of his transformation into a morally ambiguous figure. The analysis aims to shed light on how trauma influences not only behavior but also deep psychological processes.